2007
DOI: 10.1128/jcm.00525-07
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Aichi Viruses from Fecal Specimens Collected in Japan, Bangladesh, Thailand, and Vietnam

Abstract: Aichi virus is a new member of the family Picornaviridae, genus Kobuvirus, and is associated with human gastroenteritis. This study detected Aichi virus in 28 of 912 fecal specimens which were negative for rotavirus, adenovirus, norovirus, sapovirus, and astrovirus and were collected in Japan, Bangladesh, Thailand, and Vietnam during 2002 to 2005.Aichi virus, a small round virus about 30 nm in diameter, was first recognized in 1989 as the cause of oyster-associated nonbacterial gastroenteritis in humans (8-10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 12 publications
5
83
3
Order By: Relevance
“…The Aichi virus is known as an agent causing gastroenteritis associated with oyster consumption (43). Its involvement in gastroenteritis in children has recently been shown, but this remains a rare event (2,28,35). These recent data and our present results support the idea of a role of Aichi virus in cases of gastroenteritis and suggest that oysters may not be the only vector for transmission of the virus.…”
Section: Discussionsupporting
confidence: 81%
“…The Aichi virus is known as an agent causing gastroenteritis associated with oyster consumption (43). Its involvement in gastroenteritis in children has recently been shown, but this remains a rare event (2,28,35). These recent data and our present results support the idea of a role of Aichi virus in cases of gastroenteritis and suggest that oysters may not be the only vector for transmission of the virus.…”
Section: Discussionsupporting
confidence: 81%
“…To date, the genus Kobuvirus consists of 2 species, Aichi virus and bovine kobuvirus (2). The Aichi virus is associated with acute gastroenteritis in humans (3)(4)(5); bovine kobuvirus infection has been detected only in cattle (1). Only 1 report has described the discovery and epidemiologic features of bovine kobuvirus (1).…”
Section: Bovine Kobuviruses From Cattle With Diarrheamentioning
confidence: 99%
“…Just as in adults, there has been limited knowledge about the epidemiology of Aichi virus infection in children. Its presence in fecal specimens of children suffering from diarrhea has been demonstrated in several Asian countries (5,13), in Brazil (4), and in France (1). Nevertheless, despite the low incidence of Aichi virus encountered in sporadic and epidemic cases, several studies of seroprevalence conducted in Japan (12), Germany (4), Spain (J. Buesa, personal communication, 28 September 2007), and more recently in France (2) indicated that this virus is quite common.…”
mentioning
confidence: 99%